The life of the institutional forest-farming community to reserve the forest properly with the agroforestry concept (Studi in the Balesari Village – Malang Regency) - Sonny Leksono; Mohammad Rosyidi; Rita Alfin (AMCA Journal of Community Development, 2023)
A classic environmental phenomenon afflicts communities around mountainous forests in Indonesia. Needs institutional management to achieve a prosperous life based on environmental conservation took place in the people as inhabitants hold a potential risk, bearer subject of 'deforestation and degradation or, in contrast, acts as a conservation agent of 'reforestation and revitalization' in the capacity of forestry landfill. This non-positivistic qualitative study revealed the unique actions of "institutional and agroforestry" actors. The approach takes a paradigm that places forest communities as the research subjects. These main subjects feel and then deal directly with all forestry problems regarding deforestation and land degradation. Those forest people who live and depend on forests need attention and social justice. The research process includes tracking history, organization, and interaction between or among the groups of forest farmers in their institutions. The authentic findings of this study are: It needs a real activity, norms and ethics for the business process. So it can foster a synergy of positive externality values in maintaining the traditional forest conservation rules. Furthermore, developing them suits the concept of agroforestry as productive farming in a sustainable environment and adaptive to the character of the forest's natural behaviour.